2016
DOI: 10.1097/qai.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Estimates of Life Expectancy After HIV Diagnosis

Abstract: Introduction Using National HIV surveillance system data we estimated life expectancy and average years of life lost among person diagnosed with HIV infection during 2008–2011. Methods Population-based surveillance data, restricted to persons with diagnosed HIV infection age 13 years or older, from all 50 states and D.C. were used to estimate life expectancy after HIV diagnosis using the life table method. Generated estimates were compared with life expectancy in the general population in the same calendar y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 32 publications
3
44
1
1
Order By: Relevance
“…In the era of antiretroviral therapy (ART), there have been striking decreases in acquired immune deficiency syndrome (AIDS)‐related mortality 1, 2, 3 and prolongation of life expectancy 4, 5, 6, 7 for people living with HIV infection (PLWH). With this, there has been a shift in distribution of causes of death toward non‐AIDS‐defining events (NADEs) 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of antiretroviral therapy (ART), there have been striking decreases in acquired immune deficiency syndrome (AIDS)‐related mortality 1, 2, 3 and prolongation of life expectancy 4, 5, 6, 7 for people living with HIV infection (PLWH). With this, there has been a shift in distribution of causes of death toward non‐AIDS‐defining events (NADEs) 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…While life expectancy and health-related quality of life (HRQOL) of persons living with HIV or AIDS (PLWHA) has significantly improved (Samji et al, 2013; Siddiqi, Hall, Hu, & Song, 2016), the prevalence of certain risk behaviors and co-morbid conditions exceeds the general population (Burkhalter, Springer, Chhabra, Ostroff, & Rapkin, 2005; Centers for Disease Control and Prevention, 2016; O’Cleirigh, Magidson, Skeer, Mayer, & Safren, 2015). Compared to the adult general population, PLWHA are more likely to smoke and less likely to quit smoking (Mdodo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in medical care for people living with HIV, which include advances in treatment, decreased rates of AIDS-related deaths (1), and increased life expectancy (2,3), elevated rates of non-AIDS complications such as cardiovascular disease (CVD) are increasingly prevalent in this population (4,5). Large epidemiological studies have shown that rates of acute myocardial infarction (AMI) are 1.5 to 2 times higher in HIV patients compared to those without HIV even after controlling for traditional cardiovascular risk factors such as hypertension, diabetes, and smoking (6,7).…”
Section: Introductionmentioning
confidence: 99%